Oxygen transport in electroceramics investigated by electrochemical 18O/16O isotope exchange and ToF‐SIMS. (1st August 2012) - Langer‐Hansel, K.; Schintlmeister, A.; Fleig, J.; Hutter, H.
<x xml:space="preserve">Abstract</x> In this contribution 18O tracer diffusion experiments were carried out on electroceramics and analysed by time‐of‐flight secondary‐ion mass spectrometry. For the analysis, different operation modes of the Bi liquid metal ion gun were compared with respect to signal intensity, lateral resolution and mass resolution. Procedures for obtaining a basic estimation of the 18O fraction are given. It is shown that high target current, i.e. high number of primary ions, increases the accuracy and the precision of the determination of the 18O fraction if the observed count rate of the 16O signal is lower than 0.95 cts/shot. As an example, 18O diffusion profiles at the surface of a ZrO2:9.5mol%Y2O3 single crystals are shown. Copyright © 2012 John Wiley & Sons, Ltd.